2022
DOI: 10.1080/17435390.2022.2030821
|View full text |Cite
|
Sign up to set email alerts
|

NiONPs-induced alteration in calcium signaling and mitochondrial function in pulmonary artery endothelial cells involves oxidative stress and TRPV4 channels disruption

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 61 publications
5
19
0
Order By: Relevance
“…In addition, we showed that NiONP exposure significantly increased global ROS and mitochondrial O 2 − production as compared to control cells. These results are in line with previously published data regarding NiONP exposure [24]. However, in cells exposed to NiONPs under pathological conditions, the increase in ROS and mitochondrial O 2 − production was greater than in HPAEC under physiological conditions.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In addition, we showed that NiONP exposure significantly increased global ROS and mitochondrial O 2 − production as compared to control cells. These results are in line with previously published data regarding NiONP exposure [24]. However, in cells exposed to NiONPs under pathological conditions, the increase in ROS and mitochondrial O 2 − production was greater than in HPAEC under physiological conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Prior to use, stock suspensions were vortexed, sonicated at 3 × 30 s (Vibracell 75186, 130 W, 56-60 Hz), and diluted in ECGM extemporaneously at appropriate concentrations (0.5-5 µg/cm 2 ). The NiONPs were previously characterized by Germande et al, 2022 [24]. The hydrodynamic size distribution of NiONPs suspended in ECGM was determined at a concentration of 5 µg/cm 2 by dynamic light scattering (DLS) using a VASCO particle-size analyzer from Cordouan Technologies ® (Pessac, France).…”
Section: Nio Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ca 2+ is a versatile and ubiquitous second messengers, and Ca 2+ changes play an interactional role in multiple biological processes [58]. Cytosolic Ca 2+ increase is always related with increased total ROS levels, cell apoptosis, energy metabolism dysfunction, ER stress, and mitochondrial dysfunction, and these processes will interactively further induce cytosolic Ca 2+ increase via regulating Ca 2+ gate by promoting the Ca 2+ leaking from the plasma membrane or ER [59,60]. Consistent with previous studies, we found increasing intracellular Ca 2+ concentration induced by TRPA1 activation in inflammation in this study, which is in accordance with high levels of OS markers, apoptosis, ER stress, and mitochondrial dysfunction and with TRPA1 inhibitor, and the above cell functions significantly decreased combined with decreased intracellular Ca 2+ concentration.…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%